Label-free electrochemical aptasensor based on cellulose nanocrystal-modified paper-based device for Salmonella Typhimurium detection in food samples - Jampasa, Sakda; Sangthong, Natthawut; Ozer, Tugba; Panphut, Wattana; Naorungroj, Sarida; Ngamrojanavanich, Nattaya; Kaneta, Takashi; Chailapakul, Orawon; Wonsawat, Wanida (ELSEVIER, 2025)
Salmonella Typhimurium (S. Typhimurium) is a pathogenic bacterium associated with food contamination and severe illnesses. Given its low infectious dose, monitoring this bacterium is critical. Conventional detection methods often involve labor-intensive and time-consuming enzyme-linked immunoassays, further highlighting the need for more efficient alternatives. In this study, we developed a paper-based electrochemical aptasensor utilizing a label-free format, enhanced with carboxyl (COOH)-functionalized cellulose nanocrystals, as an innovative platform for detecting S. Typhimurium. The device was custom-designed and fabricated using a wax printing technique on Whatman filter paper, yielding a disposable and desirable paper-based analytical device (PAD). COOH-cellulose nanocrystals were applied to the PAD surface to directly immobilize an aptamer probe specific to Salmonella, employing effective EDC/NHS standard chemistry without requiring additional modifications. The subsequent formation of a half-sandwich immunocomplex (aptamer/Salmonella) induces a highly insulated layer on the PAD surface, suppressing the redox mediator signal response of [Fe(CN)6]3-/4- in a Salmonella concentration-dependent manner, with detectable ranges from 10 to 109 CFU/mL and an ultra-low detection limit of 3.50 CFU/mL, as evaluated by differential pulse voltammetry. This aptasensor successfully detects the presence of Salmonella in food samples, demonstrating remarkable sensitivity, selectivity, rapid response times (30 min), and portability.
Keywords: Paper-based aptasensor; Cellulose nanocrystals; Salmonella Typhimurium; Electrochemical detection; Label-free detection; SENSITIVE DETECTION; GRAPHENE OXIDE; SENSOR; Chemistry